Upside-down ears - Connely, Neil (Maryland : Ottenheimer Publishers, Inc, 1995)
Flora, a bunny with Upside-Down Ears, pays a visit to her cousins Blaze, Nibbles, and Violet at the edge of the Carrot Patch. Here they all discover that although they might look different, they all have a great deal in common, too!
Keywords: Physical differences -- Fiction; Friendship -- Fiction; Children stories